Marketing Capability and Creativity and Innovation on the Success of Community MSMEs: (Study on MSMEs Assisted by PT Pertamina Refinery Unit (RU) II Sei Pakning) - Mandataris, Mandataris; Kasmiruddin, Kasmiruddin; Ruzikna, Ruzikna; Safitri, Syofiatul (Politeknik Negeri Batam, 2024)
The purpose of this research is to find out and see the influence of marketing ability and creativity and innovation on the success of community MSMEs (study on MSMEs fostered by PT. Pertamina RU II Sei Pakning). Sampling was done by proportional stratified random sampling. Methods of data collection is done by observation, questionnaires, interviews and documentation. The data analysis technique used is descriptive statistics and inferential statistics. The results showed that the marketing ability of MSMEs was still constrained in terms of distribution. The creativity of MSMEs is also not so good, because of the doubts of MSMEs to produce new products and the lack of ability to find solutions to the problems they face. The results of the study also stated that the ability of marketing, creativity and innovation to have a positive and significant influence on the success of MSMEs fostered by PT. Pertamina RU II Sei Pakning.